الآثار الواردة في تفسير ابن أبي زمنين: جمعاً ودراسةً -من مقدمة التفسير إلى آخر سورة النساء- - أحمد عبد الباقي سعد الـهميلي
The Quranic commentary (Tafsir) of Ibn Abi Zamanin (died in 399H) is one of the notable Quranic commentaries written during the Andalusian period. It is one of the prominent Quranic commentaries of Maliki scholars in the fourth century which is concerned with the interpretation of Quran with prophetic traditions. This Tafsir of this author is an abridgement of Quranic commentary of Yahya bin Sallam (died in 200H). The work specifically dealt with the narrations of Ibn Abi Zamanin from the noble companions of the prophet (may Allah be pleased with them) ، starting from the introduction of his Quranic commentary to the chapter of the women (Suratul Nisā'). In other words، it reviewed the traditions and traced the method adopted by Ibn Abi Zamanin through his father and from Yahya bin Salam and adjudged it according to the method of the Hadith scholars. The study is based on three methods- namely descriptive، critical and comparative methods. Meanwhile، the study’s framework is made up of preface، introduction، five chapters and the conclusion. The chapters discussed the traditions reported by the companions، their definition and their authenticity for making verdicts including the opinions of scholars regarding that. The research also disclosed the role of a prophetic tradition in the work of Ibn Abi Zamanin through the Quranic commentary، faith، recitations and linguistic meanings. Besides، this study examined the weak and fabricated traditions reported from the companions in this Quranic commentary. It also looked into how the author used to cite the traditions in many of his works، compared the latter with his Quranic commentary and verified the extent of his acceptance and rejection of the weak traditions. In the end، the study made a comparison between the reports given by Ibn Abi Zamanin in respect of the traditions said to have been collected from the companions and some other books، and thoroughly searched for the copies of hand-written Quranic commentaries of Yahya bin Salam and Ibn Abi Zamanin. Finally، the study has come out with the facts that the Tafsir contained 224 traditions from the Prophet’ companions. However، out of the traditions، 59 were verified. Then، the outcome is that 33 of them are considered authentic; one (1) is authentic by virtue of another Hadith; six (6) are good; two (2) are good by virtue of another Hadith; nine (9) are weak; one (1) is very weak; two (2) are considered suspended traditions; one (1) is a denounced tradition, while four (4) are regarded as fabricated traditions.